Resurgence of Diphtheria: A Narrative Review - Sajid, Khandaker Md Tasnim; Jahan, Tarana (Journal of Monno Medical College, 2025)
Changes in the epidemiology of diphtheria are occurring worldwide. Waning immunity to diphtheria was observed over time after childhood vaccination. After immunization in childhood, appropriate re-vaccinations are omitted for various reasons. Fear of adverse reactions in the course of diphtheria booster vaccination bears much of the responsibility. A large proportion of adults in many industrialized and developing countries are now susceptible to diphtheria. Inadequate boosting of previously vaccinated individuals may result in increased risk of acquiring the disease from a carrier, even if adequately immunized previously. The continuous circulation of toxigenic C. diphtheriae emphasizes the need to be aware of epidemiological features, clinical signs, and symptoms of diphtheria; so that cases can be promptly diagnosed and treated, and further public health measures can be taken to contain this serious disease. Journal of Monno Medical College June, 2024;10 (2):94-103